Improvement of Power Quality in an Autonomous System using DSATCOM - Ghosh, Sourav; Mahata, Saumyadeep; Das, Epsita; Banerji, Ambarnath (International Journal of Computer Sciences and Engineering, 2025)
This paper discusses an control scheme of a Distribution Static compensator (DSTATCOM) to rectify unbalance and improve power quality by reducing harmonics at load end of an autonomous system. This scheme does not require any new hardware implementation. In this proposed technique.Three phase load current active and reactive components are dissociated and are used in association with PI controllers and simple arithmetical operators produces carrier signals for and PWM controller. This signal along with the sinusoidal voltage is used to generate firing pulses for the IGBT switches of a 3 level voltage source inverter (VSI). The result shows that the scheme is effective in reducing total harmonic distortion (THD) in voltage at PCC, load current and competent to overcome unbalance at load end.